The Effects of Altitude Training on Blood Components and Performance of Elite Rowing Athletes: Systematic Literature Review - Rifqi Harits Taufiqurahman; Dede Rohmat Nurjaya; Pipit Pitriani; Agus Rusdiana (Universitas Negeri Semarang, 2025)
Rowing athlete performance is greatly influenced by aerobic capacity, explosive strength, and precise technical coordination. One strategy widely used to support performance improvement is altitude training, namely training in hypoxic conditions through the Live High-Train Low (LHTL), Live High-Train High (LHTH), and Intermittent Hypoxic Training (IHT) methods. Hypoxic exposure is believed to stimulate an increase in erythropoietin (EPO), which in turn increases hemoglobin (Hb), hematocrit (Hct), and total hemoglobin mass (Hbmass), thereby optimizing the body's oxygen transport capacity. This study aims to systematically examine the effect of altitude training on blood components and the performance of elite rowing athletes. The study was conducted using a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines. Data sources were obtained through the Publish or Perish tool with a publication year range of 2015–2025, and inclusion criteria focused on Randomized Controlled Trial (RCT) studies examining the effects of altitude training on elite rowing athletes. The results of the analysis showed that the LHTL method with a duration of 3–4 weeks and hypoxic exposure of ≥12 hours per day provided a significant increase in Hb, Hct, Hbmass, as well as aerobic capacity such as VO₂max and peak power output. However, there are variations in individual responses between